Prevalence of Type 2 Diabetes Mellitus in Women with Osteoporosis: A Cross-Sectional Study - Kanwal Ayub, Hina Memon, Khadija Bano, Ghulam Sughra Bhellar, Abdullah, Zaira Ayub, (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To determine the prevalence of type 2 diabetes mellitus (T2DM) in postmenopausal women with osteoporosis and evaluate its association with metabolic and inflammatory parameters. Material and Methodology: This Descriptive cross-sectional study was conducted in the Department of Obstetrics and Gynecology, Jinnah postgraduate medical Center (JPMC) Karachi, from 31 May 2021 to 30 November 2021. A total of 147 postmenopausal women aged 45–70 years with established osteoporosis were enrolled through non-probability consecutive sampling. Patients with secondary causes of bone loss were excluded. Data were collected using a structured proforma. T2DM diagnosis was based on fasting/random blood sugar and HbA1c criteria. Associations between T2DM and variables including age, residence, BMI, duration of osteoporosis, hypertension, CRP, magnesium levels, and vitamin D were analyzed using chi-square test. A p-value ≤ 0.05 was considered statistically significant. Results: Out of 147 osteoporotic women, 61 (41.5%) had type 2 diabetes mellitus. T2DM was significantly associated with hypertension (p = 0.02), raised CRP levels (p = 0.01), and hypomagnesemia (p = 0.02). No significant association was observed with age, BMI, residence, vitamin D deficiency, or other clinical parameters. Conclusion: A high prevalence of type 2 diabetes was found among osteoporotic women. The significant associations with hypertension, systemic inflammation, and hypomagnesemia highlight the need for comprehensive screening and metabolic evaluation in these patients to guide timely interventions and improve bone and metabolic health outcomes. Keywords: T2DM, Osteoporosis, CRP, Mg, Vit D, HTN, Inflammation